The United States Government uses PIM research on poverty, nutrition, demographics, and safety nets to design the Global Food Security Strategy Bangladesh Country Plan - CGIAR Research Program on Policies, Institutions, and Markets (2018)
USAID extensively consulted findings on poverty, nutrition, demographics, and safety nets from the IFPRI/PIM Bangladesh Policy Research and Strategy Support Program in the formulation of the United States Government Global Food Security Strategy Bangladesh Country Plan. Both the choice of the target location within the country and some thematic components of the Plan were informed by PIM research.